Reduction in the tilting of oxygen octahedron and its effect on bandgap with La doping in SrSnO3. Issue 11 (1st August 2020) - Kumar, Yogesh; Kumar, Ravi; Choudhary, R.J.; Thakur, Anup; Singh, A.P.
Abstract: Tilting of oxygen octahedra in perovskite is known to deteriorate the transparent conducting oxide (TCO) properties of perovskites. Traditional wisdom suggests that doping with an ion of larger size can reduce this tilting in stannates. In this study, we show that doping with smaller La-ion at Sr-site in SrSnO3 can also lead to a reduction in tilting, thereby improving the transport properties of the material. Structural and optical properties of La-doped strontium stannate (La x Sr1− x SnO3, with x  = 0, 0.03 and 0.07) bulk, powder samples are presented. Rietveld refinement of the x-ray diffraction pattern was performed. A reduction in oxygen octahedral tilting with La-doping was observed from the refinement results. As a result of this reduction in oxygen octahedral tilting, changes in Sn–O and Sr–O bond lengths were observed. X-ray photoelectron spectroscopy (XPS) revealed that Sn 4+ reduces to Sn 2+ to balance the charge neutrality. The percentage contribution of Sn 2+ was found to increase with doping, which suggests that La-dopant generates n -type conductivity in the material. Valence band spectroscopy (VBS) shows the n –type nature of the samples. Raman and Fourier transform infrared spectroscopy results support the XRD results, exhibiting a blue shift in their bands, which is attributed to the change in bond lengths and consequently, to a reduction in the tilting. Optical properties were studied by UV–Vis spectroscopy. The materials are transparent in the visible range, with bandgaps in the range of 3.87–3.97 eV.